Financial Literacy, Financial Technology, and Business Performance: Does Financial Inclusion Mediate? - Asgara, Yelli Fitri; Tasman, Abel (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to examine the influence of Financial Inclusion in mediating the impact of Financial Literacy and Financial Technology on the Business Performance of Micro, Small, and Medium Enterprises (MSMEs) in Padang City. This study uses a quantitative research method with a non-probability sampling technique. The study was conducted by distributing questionnaires to 115 respondents who were micro, small, and medium enterprises in Padang City. Data processing was carried out using Smart PLS (Partial Least Squares) software. The results of the study indicate that, Financial Literacy has a positive and significant effect on Business Performance of MSMEs in Padang City Financial Technology has a negative but insignificant effect on Business Performance of MSMEs in Padang City Financial Inclusion has a positive and significant effect on Business Performance of MSMEs in Padang City Financial Literacy has a positive effect on Financial Inclusion of MSMEs in Padang City. Financial Technology positively and significantly affects Financial Inclusion. Financial Inclusion does not mediate the effect of Financial Literacy on Business Performance of MSMEs in Padang City. Financial Inclusion mediates the influence of Financial Technology on the Business Performance of MSMEs in Padang City.